Wykorzystanie miary Braya-Curtisa do oceny miejsca Polski w UE pod względem innowacyjności gospodarki - Markowska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the procedure, based on Bray-Curtis distance measure, which facilitates grouping countries into sets representing different distance from a selected object (Poland, "leader") with regard to economy innovation. It also presents the empirical example allowing for distinguishing groups of countries with respect to a distance which separates Poland from these countries in the field of innovation. The paper also includes an assessment of both distance and position of Polish economy in relation to Sweden - the innovation "leader". (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 19-30